Power vegan meals : high protein, plant-based recipes for a stronger, healthier you - Sozer, Maya (Page Street Publishing Co, 2017)
In Power Vegan Meals, Maya creates easy meals that are high in protein and flavor and low in prep time, so they're great for athletes as well as healthy, active people. Drawing inspiration from international cuisine and comfort food favorites, Maya has crafted over 75 diverse and flavorful gluten-free, soy-free, dairy-free and plant-based recipes that will keep you energized throughout the day. Recipes range from BBQ Jackfruit with Red Cabbage Slaw and guilt-free Peanut Butter Chocolate Fudge Bites to probiotic-rich Home-Brewed Kombucha and Kimchi. Maya's Four-Seed Granola Bars provide the pre-workout fuel you need to train hard and her Pad Thai and Toasted Chickpea Tacos with Mango Relish make international favorites accessible, leaving you feeling happy, healthy and ready to take on the rest of your day. Whether you're new to the vegan lifestyle or are looking for a way to increase your protein intake, Power Vegan Meals is here to help you meet your health and fitness goals with energizing high- protein and probiotic-rich recipes.